2012
DOI: 10.2174/1876214x01205010001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Vicinal Diols by Cerium(IV) in Aqueous Acidic Media Catalyzed by Rhodium(III)

Abstract: Potential of rhodium(III) chloride in catalyzing, in aqueous sulfuric acid medium, the oxidation of vicinal diols, and the kinetics of reaction of cerium(IV) with propane-1,2-diol and butane-2,3-diol catalyzed by rhodium(III) chloride was investigated. Data show that the reactions follow first order kinetics with respect to low cerium(IV) for lower concentrations, but a further increase in the oxidant concentration retards the reaction velocity. The reaction rate shows direct proportionality with respect to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rhodium(III) is an effective catalyst for Ce(IV) oxidations of vicinal diols in aqueous sulfuric acid medium. [90,91] annulation with gem-difluoroacrylate to form 5methylene-1H-pyrrol-2(5H)-one derivatives. [92] Annulations to azolopyrimidines via rhodium(III)catalysed imidoyl C−H activation was also reported.…”
Section: Rhodium-based Catalysismentioning
confidence: 99%
“…Rhodium(III) is an effective catalyst for Ce(IV) oxidations of vicinal diols in aqueous sulfuric acid medium. [90,91] annulation with gem-difluoroacrylate to form 5methylene-1H-pyrrol-2(5H)-one derivatives. [92] Annulations to azolopyrimidines via rhodium(III)catalysed imidoyl C−H activation was also reported.…”
Section: Rhodium-based Catalysismentioning
confidence: 99%
“…Kinetics and mechanistic studies on oxidation of various organic substrates by cerium salts have been reported in perchloric acid 1,2,3,4 , sulphuric acid 5,6,7,8 and nitric acid 9,10 . Selective oxidation of substrates in the aqueous solution is significant in order to investigate the proper and efficient reactants and their species like oxidants, catalysts activity of the different solvent systems.Cerium (IV) ion has been used for oxidation of many organic compounds in the form of ceric ammonium nitrate and ceric ammonium sulphate.…”
Section: Introductionmentioning
confidence: 99%